Digital Marketing Usaha Kecil dan Menengah Melalui Media Sosial - Dirvi Surya Abbas; Arry Eksandy; Mulyadi Mulyadi; Imam Hidayat; Riski Ulan Sari (Jurnal Pemberdayaan Umat, 2022)
Purpose : To begin, raise customer knowledge of their preferences for convenience and simplicity of access to product/service information. Method : It comprises, namely, of first socializing consumer demands in order to have easy access to knowledge about products/services. Second, offering information about market circumstances and client demand to individuals who wish to locate the existence of the desired product online more successfully. Result : First, learn more about what customers desire in terms of comfort and simplicity of access to product/service information. Second, grasp market circumstances in terms of customer wants for being more effective in locating the presence of the items they are seeking for online. Third, the capacity to apply information about the desires of customers who want to connect with brands/brands and items online to various MSME actors. Conclusion: Business players in Pasarkemis District, Tangerang Regency may comprehend the relevance of digital marketing for small and medium-sized firms through social media in the operations of their corporate units by offering complete socialization